3(-2x-2)=x+3

Simple and best practice solution for 3(-2x-2)=x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-2x-2)=x+3 equation:


Simplifying
3(-2x + -2) = x + 3

Reorder the terms:
3(-2 + -2x) = x + 3
(-2 * 3 + -2x * 3) = x + 3
(-6 + -6x) = x + 3

Reorder the terms:
-6 + -6x = 3 + x

Solving
-6 + -6x = 3 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-6 + -6x + -1x = 3 + x + -1x

Combine like terms: -6x + -1x = -7x
-6 + -7x = 3 + x + -1x

Combine like terms: x + -1x = 0
-6 + -7x = 3 + 0
-6 + -7x = 3

Add '6' to each side of the equation.
-6 + 6 + -7x = 3 + 6

Combine like terms: -6 + 6 = 0
0 + -7x = 3 + 6
-7x = 3 + 6

Combine like terms: 3 + 6 = 9
-7x = 9

Divide each side by '-7'.
x = -1.285714286

Simplifying
x = -1.285714286

See similar equations:

| (a-8/12)=(2a+5/3) | | -6x+3=18 | | 6/16= | | 15(x-3)=-8-7 | | 7x+4-5=7y-8 | | (4t^2-t-9)(4t^2+4t-1)= | | x^2+2.25-36=0 | | 60+10x=5(x+20) | | -3(c-6)=-3-6 | | -5x-7=2x+14 | | 3x-7-5x=3-4x | | 4(a-3)=8a-(4a+12) | | 3[3u-6]=18 | | 14x+2x=-6-3x | | (3x-4)(5x^2-2x+6)= | | 7x+4-5=2x-2 | | 8y+4=7y-8 | | -12+8x=-6(8x+2)+5x | | 7y-4+6=2y+4 | | .6w+2=26 | | ln(13)-ln(2x)=ln(52) | | 3x^2-4=4x | | 8+8q=9+7q | | m^2+6m-91= | | -5=x/2-5 | | -8c+5=-2-4c | | 38-6b=4(4b+4) | | x+.80(2)=.90(x+2) | | 5x^2y^3(2xy^3+3x^4y)= | | 8-10x=84-38x | | x+47=7x-13 | | x^2-3x+4=5 |

Equations solver categories